Epidemiology and transmission of carbapenemase-producing enterobacteriaceae in a health care network of an acute-care hospital and its affiliated intermediate- and long-term-care facilities in Singapore - Aung, Aung-Hein (2022)
Movement of patients in a health care network poses challenges for the control of carbapenemase-producing Enterobacteriaceae (CPE). We aimed to identify intra- and interfacility transmission events and facility type-specific risk factors of CPE in an acute-care hospital (ACH) and its intermediate-term and long-term-care facilities (ILTCFs). Serial cross-sectional studies were conducted in June and July of 2014 to 2016 to screen for CPE. Whole-genome sequencing was done to identify strain relatedness and CPE genes (blaIMI, blaIMP-1, blaKPC-2, blaNDM-1, and blaOXA-48). Multivariable logistic regression models, stratified by facility type, were used to determine independent risk factors. Of 5,357 patients, half (55%) were from the ACH. CPE prevalence was 1.3% in the ACH and 0.7% in ILTCFs (P = 0.029). After adjusting for sociodemographics, screening year, and facility type, the odds of CPE colonization increased significantly with a hospital stay of ≥3 weeks (adjusted odds ratio [aOR], 2.67; 95% confidence interval [CI], 1.17 to 6.05), penicillin use (aOR, 3.00; 95% CI, 1.05 to 8.56), proton pump inhibitor use (aOR, 3.20; 95% CI, 1.05 to 9.80), dementia (aOR, 3.42; 95% CI, 1.38 to 8.49), connective tissue disease (aOR, 5.10; 95% CI, 1.19 to 21.81), and prior carbapenem-resistant Enterobacteriaceae (CRE) carriage (aOR, 109.02; 95% CI, 28.47 to 417.44) in the ACH. For ILTCFs, presence of wounds (aOR, 5.30; 95% CI, 1.01 to 27.72), respiratory procedures (aOR, 4.97; 95% CI, 1.09 to 22.71), vancomycin-resistant enterococcus carriage (aOR, 16.42; 95% CI, 1.52 to 177.48), and CRE carriage (aOR, 758.30; 95% CI, 33.86 to 16,982.52) showed significant association. Genomic analysis revealed only possible intra-ACH transmission and no evidence for ACH-to-ILTCF transmission. Although CPE colonization was predominantly in the ACH, risk factors varied between facilities. Targeted screening and precautionary measures are warranted.